The Effect of Institutional Ownership, Debt Covenant and Growth Opportunity on Accounting Conservatism - Gracela Mayaniputri Tamur (Green Publisher Indonesia, 2021)
This study aims to analyze the positive effect of institutional ownership on accounting conservatism, analyze the negative effect of debt covenants on accounting conservatism, and analyze the effect of growth opportunities on accounting conservatism.The population in this study are companies listed in BUMN in the 2016 – 2018 financial year. All BUMN companies listed on the IDX are used. Sampling was carried out using purposive sampling method and had certain criteria. The data collection method used is the documentation method from electronic media. The data was obtained from the internet (www.idx.go.id and company website). Data analysis using multiple linear regressionanalysis. The discussion that has been stated, the following conclusions can be drawn; 1). Institutional ownership structure has no effect on accounting conservatism. 2). Debtcovenants have no effect onbaccounting conservatism. 3). Gross opportunity has a significant positive effect on accounting conservatism